(untitled) - Johansen, Iris (New York, 2002)
When a government official requests her unique skills of reconstruction to identify an unknown murder victim, forensic sculptor Eve Duncan is drawn into a deadly web of betrayal, intrigue, and murder as she tries to unlock the deadly secrets that someone will do anything to keep hidden.
Keywords: Facial reconstruction (Anthropology),Tái tạo khuôn mặt (Nhân loại học),Duncan, Eve (Fictitious character),Eva Duncan (Nhân vật hư cấu); Fiction,Tiểu thuyết,Fiction,Tiểu thuyết